The Spillover Effect of Global Uncertainty on BRICS Stock Markets - Allah Ditta Nawaz; Niaz Ahmed Bhutto; Shabeer Khan (Faculty of Economic and Business, 2023)
Using monthly data spanning from 1993 to 2021 and employingthe DCC-GARCH model, this study examines the role ofEconomic Policy Uncertainty (EPU) as a potential exogenousfactor impacting the correlation of Brazil, Russia, India, andChina (BRIC) economies’ stock markets, which is new to theliterature. Further, this dynamic correlation series is used as adependent variable while EPU of BRIC and USA is used as anindependent variable by utilizing the autoregressive distributedlag (ARDL) model. The study finds a positive and significantshort-run as well as the long-run impact of Russia’s and theUS’s EPU on their stock markets. In other words, as the EPUof the USA increases, the correlation of BRIC with the USAStock Market and the World Stock Market increases, suggestingminimum diversification opportunities for the investors. Thestudy also recommends that investors diversify their portfoliosby considering cross borders assets avenues to gain maximumreturns and reduce portfolio risk.JEL Classification: E44, C32, E52, E60, E62, C58How to Cite:Nawaz, A. D., Bhutto, N. A., & Khan, S. (2023). The Spillover Effect of Global Uncertainty on BRICS Stock Markets. Etikonomi, 22(1), 45–64. https://doi.org/10.15408/etk.v22i1.24617.